Telemedicine units for COVID-19: An experience from Madhya Pradesh - Saxena, Sourabh; Srivastava, Karishma; Dilbagi, Roshni; Saxena, Ashish (Indian Journal of Community Health, 2020)
On 31st December 2019, the World Health Organization (WHO) China Country Office was informed of cases of pneumonia of unknown aetiology detected in Wuhan City, Hubei Province of China.(1) The first cases of COVID-19 outside of China were identified on January 30 in India and it has spread to 210 countries in all world regions by 10th April 2020, with more than 1.6 million confirmed and more than 0.1 million deaths worldwide.(2) Disasters and pandemics pose exceptional challenges to providing health care. Though telemedicine will not solve them all, it is well suited for scenarios in which medical practitioners can evaluate and manage patients. Previous work has specifically described the potential for using telemedicine in disasters and public health emergencies, wherein Patients prioritize convenient and inexpensive care, whether in-person visits becomes the last option for meeting patient needs.(3,4)